2022
DOI: 10.22190/fueo210920003o
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Dependence of Oil-Food Price Dynamics in Africa's Net Oil-Exporting Countries

Abstract: The determinants of food prices have attracted sizeable debates among scholars over the last three decades. However, many of these studies ignore the possibility that the impact of oil prices on food prices could vary across the food price distribution. The paper employs a quantile regression technique to ascertain whether food prices respond to the potential heterogeneous impact of crude oil price changes in the six selected African net oil-exporting countries. The coefficient of negative oil price shocks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Studies have further examined the connectedness between oil and food prices in Africa and Nigeria (Rangasamy, 2010;Durevall et al, 2013;Alper et al, 2016;Udoh and Egwaikhide, 2012;Binuomote and Odeniyi, 2013;Nwoko et al, 2016;Fasanya and Akinbowale, 2019;Tule et al, 2019;Adeosun et al, 2021a;Ogede and Ajayi, 2022). Alper et al (2016) showed that high food prices are driven by non-tradable foods, and they further observed an incomplete transmission from world food and oil prices and the exchange rate to local food prices in SSA.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have further examined the connectedness between oil and food prices in Africa and Nigeria (Rangasamy, 2010;Durevall et al, 2013;Alper et al, 2016;Udoh and Egwaikhide, 2012;Binuomote and Odeniyi, 2013;Nwoko et al, 2016;Fasanya and Akinbowale, 2019;Tule et al, 2019;Adeosun et al, 2021a;Ogede and Ajayi, 2022). Alper et al (2016) showed that high food prices are driven by non-tradable foods, and they further observed an incomplete transmission from world food and oil prices and the exchange rate to local food prices in SSA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Applying the augmented Phillips curve framework, Tule et al (2019) showed that agricultural commodities predict food inflation significantly, whereas Adeosun et al (2021a) revealed weak predictive pass-through from oil prices to food prices in the short-term. More recently, Ogede and Ajayi (2022) observed that food prices react to the heterogenous effect of oil price volatility in six African net oil-exporting economies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations